Outcomes following surgical repair using layered closure of unrepaired 4th degree perineal tear in rural western Uganda. Issue 11 (November 2016) - Goh, Judith; Tan, Stephanie; Natukunda, Harriet; Singasi, Isaac; Krause, Hannah
Abstract Introduction In many rural low-income countries, perineal tears at time of vaginal birth are not repaired at time of delivery. The aims of this study are to describe the surgical technique for management of the unrepaired 4th degree tear, performed without flaps, and short-term follow up on anal incontinence symptoms using a validated questionnaire. Methods Women presenting to fistula camps in western Uganda with unrepaired 4th degree tears were interviewed using the Cleveland Clinic Continence Score. Interviews were undertaken pre-operatively, at 4–6 weeks post-operatively and 12 months following surgery. Repair of the 4th degree tear was performed in layers, with an overlapping anal sphincter repair and reconstruction of the perineal body, without flaps. All women were examined prior to discharge. Results 68 women completed pre-operative Cleveland Clinic Continence Scores. Prior to surgery, 59 % of women complained of daily incontinence to solid stools. Over 70 % of women complained of restriction to lifestyle due to the unrepaired 4th degree tear. About 50 % of the women are rejected by their husbands because of the condition. Only 1 woman had wound breakdown on Day 2. At 4 to 6 weeks follow-up, 61 women were contacted and all reported perfect continence. Conclusion This study highlights the hidden problem of unrepaired 4th degree tears in rural areas of low-income countries where most deliveries are undertaken in the village without professional health care workers. These tears have significant impact on quality of life and anal incontinence. Short-term outcomes following surgical repair using a layered closure are promising.